HUBUNGAN INTER DIALITIC WEIGHT GAINS (IDWG) DENGAN TERJADINYA KOMPLIKASI DURANTE HEMODIALISIS PADA PASIEN GINJAL KRONIK - Wibowo, Harry Permana (Universitas Prima Indonesia, 2020)
Weight gain is based on dry weight. When the body has to bear excess fluid between two dialysis times, this is what is called interdialitic body weight / Inter Dialitic Weight Gain (IDWG). IRR in 2015 noted the most frequent complication in hemodialysis durante was hypertension (38%), followed by hypotension (15%), where the etiology of the two complications above is very closely related to the number of ultrafiltration. The purpose of this study was to determine the relationship between inter dialitic weight gains (IDWG) with the occurrence of complications of durante hemodialysis. By using a research design analytic method that uses a cross sectional approach. The sampling technique uses total sampling, in which 60 respondents measured body weight and blood pressure and observed whether experiencing complications durante hemodialysis. Furthermore, the results of observations are written in the observation sheet and tested by statistical data with the Chi-Square Test. The results showed the majority of respondents had a moderate IDWG of 33 people (55%), of which 27 people (45%) had complications consisting of 7 people (11.7%) hypotension and 20 people (33.3%) hypertension. Statistical test results with the chi-square test showed that the value of p = 0,000, which means that there is a significant relationship between IDWG and the occurrence of complications of hemodialysis durante. Future researchers are expected to be able to further develop research on other complications that may occur related to IDWG.